Experimental investigation on heat and mass transfer in a vertical glass bubble absorber with R124-NMP pair. (April 2020) - Wang, Wei; Xu, Shiming; Wu, Xi; Jiang, Mengnan
Highlights: Heat and mass transfer of R124-NMP in a vertical glass bubble absorber have been investigated. The key operation parameters were converted into dimensionless parameters and the effects of them on heat and mass transfer of R124-NMP were investigated. Correlations for overall and two-phase volumetric mass transfer coefficients were proposed. Dimensionless absorption height was introduced to express volumetric mass transfer coefficient. Abstract: An experimental study on heat and mass transfer characteristics of R124-NMP in a vertical glass bubble absorber has been conducted under operating conditions of air-cooled absorption system. The key operation parameters, solution volumetric flow rate, temperature and mass fraction at the absorption tube entrance, vapor volumetric flow rate, orifice diameter and absorption pressure, are converted into dimensionless numbers. A sensitive study of the key operation parameters on overall heat and mass transfer coefficients and two-phase mass transfer coefficient has been performed. The overall heat and mass transfer coefficients and two-phase mass transfer coefficient increase as Re v and absorption pressure increase and decrease as orifice diameter increases. The overall heat transfer coefficient increases as Res increases and decreases as solution temperature and mass fraction increase. This trend is reversed for overall mass transfer coefficient. The increase of solution inlet mass fraction can improve the two-phase mass transfer coefficient while the solution inlet temperature affects the two-phase mass transfer coefficient slightly. On the basis of the experimental data, dimensionless empirical correlations for overall and two-phase Sherwood numbers are proposed with error bands of ±10% to calculate the volumetric mass transfer coefficient for R124-NMP bubble absorption process in a vertical bubble absorber.